Editorial to the Special Issue on “Ocular Imaging for Eye Care” (2022)
The need for fast, inexpensive, and robust medical technology is now more crucial than ever. Ocular imaging and visual performance assessment are integral parts of ophthalmic examination, and are necessary for many clinical aspects of eye care, such as ocular implant design and treatment. The recent advances in optical technologies and information processing have continuously extended their applicability to eye care. This Special Issue gathers contributions in these fields that emphasize eye care.